Tectonostratigraphic development of the Upper Triassic to Middle Jurassic in the Hoop Area, Barents Sea: Implications for understanding ultra-condensed reservoir units - Müller, Reidar; Klausen, Tore Grane; Line, Lena; Hafeez, A; Planke, Sverre; Eide, Frøydis; Stueland, Erik; Jahren, Jens; Rismyhr, Bjarte; Olaussen, Snorre (Marine and Petroleum Geology, 2022)
The most prolific reservoir intervals in the Barents Sea are found in the Upper Triassic to Middle Jurassic Realgrunnen Subgroup, deposited during a major change in the structural evolution of the basin which greatly influenced its development and distribution. The effects are evident in one of the petroleum provinces in the SW Barents Sea, the Hoop Area. Due to the condensed nature of the succession, the tectonostratigraphic evolution has been enigmatic. We use a range of different methods and dataset, including high-resolution P-Cable seismic to determine the tectono-stratigraphic evolution of the succession. Results are important for exploration and production in the Hoop Area and beyond, but also for a broader understanding of how ultra-condensed successions might evolve during long periods of non-deposition and short bursts of deposition. Seven major phases of deposition and non-deposition/erosion are defined. Stage 1 represents fluvio-deltaic deposition in the Fruholmen Formation (Norian), followed by Stage 2 with significant truncation and non-deposition, lasting up to 35 million years. Deposition resumed with the shallow marine to fluvial Nordmela and Stø formations (Pliensbachian to Bajocian), which both encapsule long periods of erosion and non-deposition (stage 3–6). Stage 7 is represented by transgression and shelf deposition in the Fuglen Formation (Bathonian). The change from a high-accommodation setting with continuous and relatively high rate of accumulation in the Triassic, to a low-accommodation setting with episodic deposition and extensive sediment cannibalization in the Jurassic, resulted in cleaner sandstones with better reservoir properties. The low-accommodation setting also enabled coarse-graded detritus from hinterlands in Fennoscandia to prograde into distal part of the basin and more amalgamation of the sands during the Jurassic. Adversely, the low accommodation setting also caused a fragmented pattern of deposition and preservation that needs to be carefully considered in subsurface ...